The Influence of Debt Contracts and Corporate Governance Mechanisms on Accounting Conservatism - Nurfatimah, Siti Nuke; Nurhayati, Enung; Syuhira, Ira (Journal Socio Humanities Review, 2023)
The purpose of this study is to provide empirical evidence regarding the effect of debt covenants and corporate governance mechanisms on accounting conservatism. The technique used in taking the sample is the quota technique. The sample used in this study is a manufacturing company in the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2017-2021 and is presented in rupiah currency. The sample used in this study was 120 financial statement data or 24 companies/methods used in this study were descriptive methods and verification methods. The data analysis technique in this study used panel data regression analysis. Based on the results of the f test, it shows that debt covenant, institutional ownership, managerial ownership, independent commissioner, audit committee and board of commissioners affect simultaneously the accounting consevatism. Based on the results of the t-test (partial) shows that institutional ownership, managerial ownership, independent commissioner, audit committee and board of commissioners have a significant positive effect on the accounting consevatism, while debt covenants have a significant negative effect on the accounting conservatism.